Effect of planar weight disparity on the conductivity fluctuations and critical parameters in the re₀.₅ y₀.₅ ba₂ cu₃ o₇-δ (re=sm, gd, dy, ho, eu, yb) (2010)
Synthesis and conductivity characterization of the RE₀.₅ Y₀.₅ Ba₂ Cu₃ O₇-δ (RE=Sm, Gd, Dy, Ho, Eu, Yb) superconducting materials are reported. Samples were produced by the standard solid state reaction method. Rietveldlike refinement of xray diffraction data permit to establish the crystalline appropriated distribution of rare earth and yttrium to create substantial planar weight disparity (PWD) in alternating layers. DC resistivity measurements reveal the improvement of the critical temperature (Tc) when substitution of exact 5050 mix of rare earth (Sm, Gd, Dy, Ho, Eu, Yb) and Yttrium is performed. A bulk Tc ≈ 94.3 K was determined by the criterion of the maximum in the temperature derivative of electrical resistivity for the analyzed samples. The correlations of the critical exponents with the dimensionality of the fluctuation system for each Gaussian regime were performed by using the AslamazovLarkin theory. The genuinely critical exponent is interpreted by the 3DXY model as corresponding with the dynamical universality class of the Emodel.